2002
DOI: 10.1089/088922202753519179
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in T Lymphocyte Profiles of Bronchoalveolar Lavage Fluid from SIV- andPneumocystis carinii-Coinfected Rhesus Macaques

Abstract: The goal of this study was to examine SIV- and Pneumocystis carinii-coinfected rhesus macaques as a model of P. carinii infection in HIV-seropositive humans. The influence of P. carinii infection on the cellular composition of bronchoalveolar lavage (BAL) fluid from SIV-infected and normal rhesus macaques was examined by flow cytometric analysis and polymerase chain reaction (PCR). BAL fluid from SIV- and P. carinii coinfected macaques showed a substantial T lymphocyte influx composed of more than 90% CD8+ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 33 publications
2
30
0
1
Order By: Relevance
“…PBMC were counted, stained, and fixed for analysis by flow cytometry. BAL fluid was processed for cell isolation as previously described (6,30). Unfractionated BAL fluid aliquots were used for bacterial, fungal, and viral culture (Antech Diagnostics, Pittsburgh, PA) and PCR detection of Pneumocystis DNA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PBMC were counted, stained, and fixed for analysis by flow cytometry. BAL fluid was processed for cell isolation as previously described (6,30). Unfractionated BAL fluid aliquots were used for bacterial, fungal, and viral culture (Antech Diagnostics, Pittsburgh, PA) and PCR detection of Pneumocystis DNA.…”
Section: Methodsmentioning
confidence: 99%
“…In a model of immunocompetent mice, cigarette exposure and Pneumocystis colo-nization resulted in greater pulmonary function deficits compared to cigarette exposure alone (4). Our laboratory has reported that in a simian immunodeficiency virus (SIV)-primate model of HIV infection, Pneumocystis colonization results in pulmonary inflammation, pulmonary function deficits, and anatomic emphysema (2,6,47,59). Factors that influence susceptibility to Pneumocystis colonization are not clearly understood.…”
mentioning
confidence: 99%
“…Further studies of T cell reconstitution in severe combined immunodeficiency (SCID) mice using splenocytes depleted of either CD4 ϩ T cells or CD8 ϩ T cells also failed to show a positive effect of CD8 ϩ T cells on protection from infection (257). In a model of HIV and Pneumocystis coinfection, we have shown that in simian immunodeficiency virus (SIV)-infected primates, Pneumocystis infection resulted in significant accumulation of CD8 ϩ T cells in BAL fluid compared to that in animals infected with SIV alone; however, the dramatic influx of CD8 ϩ T cells to the lungs in this model did not appear to be sufficient for clearance of Pneumocystis (44).…”
Section: Cd4mentioning
confidence: 96%
“…In laboratory rodents, nested PCR of oral swabs has demonstrated that close to 100% of adult rats are colonized with Pneumocystis shortly after receipt (127). Similarly, spontaneous colonization occurs in both free-living and laboratory nonhuman primates (23,44,63). In a free-living macaque colony, all animals had detectable colonization at some point over a 2-year observation period, and the duration of colonization averaged 2 months (63).…”
Section: Colonization In Animalsmentioning
confidence: 99%
“…This extended colonization period and the indolent course of the infection are very similar to those of HIV-associated PCP. Naturally acquired and experimental PCP in SIV-infected macaques shows histopathologic features similar to those seen in HIV-associated PCP (1,2,4,7,13).…”
mentioning
confidence: 97%